The Spanish Inquisition’s Attack on Liberalism. The Indictment against Benjamin Constant’s Principes de Politique - María Luisa SÁNCHEZ-MEJÍA (Cuadernos Dieciochistas)
In 1816, after close examination, the Spanish Inquisition forbade Benjamin Constant’s Principes de Politique, the most representative work of liberal ideology of its day. A careful study of the official indictment shows that in the early 19th c. the concepts of natural law and of the general will introduced by the Enlightenment were still being countered with the same arguments which had been used in the preceding century. Nonetheless, the consequences for Spain of the French Revolution would force the Inquisition to face the challenges posed by liberalism in Europe.